Design and Control of a Haptic Enabled Robotic Manipulator. (31st July 2015) - Yaqoob, Muhammad; Sher Qaisrani, Sardar Rushan; Waqas Tariq, Muhammad; Ayaz, Yasar; Iqbal, Sohail; Nisar, Sajid
Robotic surgery offers various advantages over conventional surgery that includes less bleeding, less trauma, and more precise tissue cutting. However, even surgeons who use the best commercially available surgical robotic systems complain about the absence of haptic feedback in such systems. In this paper, we present the findings of our project to overcome this shortcoming of surgical robotic systems, in which a haptic-enabled robotic system based on master and slave topology is designed and developed. To detect real-time intrusion at the slave end, haptic feedback is implemented along with a programmable system on chip, functioning as an embedded system for processing information. In order to obtain real-time haptic feedback, force and motion sensors are mounted on each joint of the master and slave units. At the master end, results are displayed through a graphical user interface, along with the physical feeling of intrusion at the slave part. Apart from the obvious applications of the current system in robotic surgery, it could also be used in designing more intuitive video games with further precise haptic feedback mechanisms. Moreover, the results presented in our work should pave the way for further scientific investigation, to provide even better haptic mechanisms.